Effects of early diagenesis on molecular distributions and carbon isotopic compositions of leaf wax long chain biomarker n-alkanes: Comparison of two one-year-long burial experiments. (February 2017) - Li, Rencheng; Fan, Jun; Xue, Jiantao; Meyers, Philip A.
Highlights: n -Alkanes in leaves of both plant species decreased during burial in soil for ∼1 yr. n -Alkane ACL values of leaves of N. affinis buried in red soil for ∼1 yr increased. n -Alkane δ 13 C of N. affinis leaves showed minimal increase during the experiment. n -Alkane distributions and δ 13 C of O. fragran leaves in lateritic soil were unchanged. Early diagenesis has little effect on δ 13 C of leaf wax alkanes 1 yr after burial. Abstract: Two burial experiments were performed to compare and contrast the effects of degradation and early diagenesis on the molecular distributions and compound specific carbon isotope compositions of leaf wax n -alkanes under different conditions. Leaves of the bamboo Neosinocalamus affinis and the shrub Osmanthus fragrans were packaged in perforated aluminum packets and buried in soil at two different subtropical locations in China. The packets were recovered after successive intervals totaling ∼1 year, and the n -alkane properties of their leaves compared to those of the fresh leaves and the surrounding soil. Concentrations of total leaf n -alkanes decreased in both experiments. The waxes of N. affinis exhibited a fairly rapid decrease in their proportions of C23 –C27 n -alkanes and increases of less than 1‰ in n -alkane δ 13 C values during the burial time. In contrast, the leaves of O. fragrans showed little change in either their molecular distributions or isotopic compositions during burial. The results of the two experiments indicate that early diagenesis can lead to losses of leaf wax biomarker n -alkanes during burial in soil but has little to no effect on their stable carbon isotopic signatures, validating the reliability of compound specific n -alkane δ 13 C values as proxies for paleoecological and paleoenvironmental reconstructions.